CODE-MIXING IN STUDENTS’ DAILY CONVERSATION AT ENGLISH DEPARTMENT OF UKI TORAJA - Elim Trika Sudarsi (Teaching English as a Foreign Language Overseas Journal, 2016)
The objectives of this research was to find out the types of code-mixing based oninsertion that used by students at English department of UKI Toraja in their dailyconversation.This research employed qualitative method. The subjects of thisresearch were the students at English department of UKI Toraja. The data wascollected by employing voice recording. The obtained data was analyzed in fourmajor phases; data collection, data reduction, data presentation and conclusion.The result of the research displayed that the types of code-mixing based oninsertion used by students at English department of UKI Toraja are insertion ofword, insertion of phrase, insertion of word repetition and insertion of shapebaster. The students tended to mix the code in their conversation but the topic ofthe conversation was commonly not changed. In spite of mixing the code that theystill kept the communication in relevant.